2001
DOI: 10.1002/1439-7633(20010903)2:9<686::aid-cbic686>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimer-Activated Solid Supports for Nucleic Acid and Protein Microarrays

Abstract: The generation of chemically activated glass surfaces is of increasing interest for the production of microarrays containing DNA, proteins, and low-molecular-weight components. We here report on a novel surface chemistry for highly efficient activation of glass slides. Our method is based on the initial modification of glass with primary amino groups using a protocol, specifically optimized for high aminosilylation yields, and in particular, for homogeneous surface coverages. In a following step the surface am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
209
1
7

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(220 citation statements)
references
References 4 publications
(6 reference statements)
3
209
1
7
Order By: Relevance
“…This dye has a quantum efficiency of 23 %, a molar absorptivity of 187,000 L mol -1 cm -1 and fluorescence excitation and emission wavelengths of 672 nm and 694 nm, respectively, in isopropanol [28].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This dye has a quantum efficiency of 23 %, a molar absorptivity of 187,000 L mol -1 cm -1 and fluorescence excitation and emission wavelengths of 672 nm and 694 nm, respectively, in isopropanol [28].…”
Section: Methodsmentioning
confidence: 99%
“…Multivalent dendrimers are attracting a great deal of interest for applications in biomedical diagnostics [27][28][29][30], pharmacology / drug delivery [31,32] [33], cancer research [34], and nanomedicine [35]. Their use in research is still unabated now, 30 years after their first reported synthesis by Vogtle [36].…”
mentioning
confidence: 99%
“…Fluorescent labeling, on the other hand, is a promising method because of its high sensitivity, ease of operation and in situ applicability. It has been widely used in biological applications [46,47], polymer chemistry [48][49][50][51], and study of self assembled monolayers [52][53][54][55].…”
Section: Surface Chemistry Modificationmentioning
confidence: 99%
“…The presence of the dendrimeric interface leads to amplification of the signal intensity as well as to improvement of the physical-chemical stability and homogeneity of the biochips. [117,118] The functionalization of the dendrimeric slides with maleimido groups was performed by Maja Köhn The degree of protein immobilization was evaluated by screening the slide for fluorescence.…”
Section: Immobilization Of Proteins On Glass Surfaces By Diels-alder mentioning
confidence: 99%